The boy and the dog - Hase, Seishu (Simon & Schuster, 2022)
Following a devastating earthquake and tsunami, a young man in Japan finds a stray dog outside a convenience store. The dog's tag says "Tamon," a name evocative of the guardian deity of the north. The man decides to keep Tamon, becoming the first in a series of owners as the dog journeys south to find the boy whom disaster tore him from. Over the course of five years, Tamon will be taken into six vastly different homes, the final one belonging to his beloved first owner, Hikaru, a boy who has not spoken since the trauma of the tsunami. An agent of fate, Tamon is a gift to everyone who welcomes him into their life. At once heart-rending and heart-warming, intimate and panoramic, suspenseful and luminous, this bestselling, award-winning novel weaves a feel-good tale of survival, resilience, and love beyond measure.